Synthesis and characterization of manganesecurcumin complex / Nor Hazwani Mohd Noor - Mohd Noor, Nor Hazwani (2010)
Curcumin are widely used in medical area but in this study focusing on photonic area. Curcumin in different ratios and temperature was prepared. The chosen ratios of Manganese: Curcumin were 1:1, 1:1.5, and 1:2 while the temperatures were room temperature and 40°C. For the ratio, only curcumin vary in mole ratio not the metal, manganese. Curcumin complex has been characterized by using spectroscopic method such as UV/Visible spectrometry, Fluorescence spectrometry, FTIR and TGA. From UV/VIS analysis, absorbance increase when increase temperature. Meanwhile, Vax decrease when the temperature increases, blue shift observed. Fluorescence analysis, the ratio of 1:2 room temperature give the high stoke's shift. In FTIR, results, have missing of peak compare to the curcumin standard. In TGA, entire complex have the decomposition. As the conclusion, room temperature was the optimum temperature and 1:2 is the best ratio.